Reciprocal Regulation Between Forkhead Box M1/NF‐κB and Methionine Adenosyltransferase 1A Drives Liver Cancer. Issue 5 (1st October 2020) - Li, Yuan; Lu, Liqing; Tu, Jian; Zhang, Jing; Xiong, Ting; Fan, Wei; Wang, Jiaohong; Li, Meng; Chen, Yibu; Steggerda, Justin; Peng, Hui; Chen, Yongheng; et al.
Abstract : Background and Aims: Forkhead box M1 (FOXM1) and nuclear factor kappa B (NF‐ĸB) are oncogenic drivers in liver cancer that positively regulate each other. We showed that methionine adenosyltransferase 1A (MAT1A) is a tumor suppressor in the liver and inhibits NF‐ĸB activity. Here, we examined the interplay between FOXM1/NF‐κB and MAT1A in liver cancer. Approach and Results: We examined gene and protein expression, effects on promoter activities and binding of proteins to promoter regions, as well as effects of FOXM1 inhibitors T0901317 (T0) and forkhead domain inhibitory‐6 (FDI‐6) in vitro and in xenograft and syngeneic models of liver cancer. We found, in both hepatocellular carcinoma and cholangiocarcinoma, that an induction in FOXM1 and NF‐κB expression is accompanied by a fall in MATα1 (protein encoded by MAT1A). The Cancer Genome Atlas data set confirmed the inverse correlation between FOXM1 and MAT1A. Interestingly, FOXM1 directly interacts with MATα1 and they negatively regulate each other. In contrast, FOXM1 positively regulates p50 and p65 expression through MATα1, given that the effect is lost in its absence. FOXM1, MATα1, and NF‐κB all bind to the FOX binding sites in the FOXM1 and MAT1A promoters. However, binding of FOXM1 and NF‐κB repressed MAT1A promoter activity, but activated the FOXM1 promoter. In contrast, binding of MATα1 repressed the FOXM1 promoter. MATα1 also binds and represses the NF‐κB element in the presence of p65 or p50. Inhibiting FOXM1 with either T0 or FDI‐6 inhibited liver cancer cell growth in vitro and in vivo . However, inhibiting FOXM1 had minimal effects in liver cancer cells that do not express MAT1A. Conclusions: We have found a crosstalk between FOXM1/NF‐κB and MAT1A. Up‐regulation in FOXM1 lowers MAT1A, but raises NF‐κB, expression, and this is a feed‐forward loop that enhances tumorigenesis.